PENGUNGKAPAN DAN AKUNTABILITAS: TINJAUAN LITERATUR ATAS PELAPORAN KEBERLANJUTAN SERTA PERILAKU PERUSAHAAN - Sukmawaty Siahaan (LAND JOURNAL, 2026)
ABSTRACT The growing emphasis on sustainability reporting has elevated non-financial disclosure as a central mechanism for enhancing corporate transparency and accountability. Beyond its communicative role, sustainability reporting is increasingly expected to influence corporate behavior by shaping managerial decision-making, strategic priorities, and organizational practices. This study presents a literature review that synthesizes prior research examining the relationship between sustainability reporting and corporate behavior across accounting, management, and sustainability disciplines. The review highlights that sustainability reporting can encourage improved accountability, risk awareness, and long-term strategic orientation; however, its behavioral impact remains uneven and context-dependent. A substantial body of literature indicates that sustainability reporting is frequently motivated by legitimacy-seeking and institutional pressures, resulting in symbolic disclosure rather than substantive organizational change. The effectiveness of sustainability reporting in driving meaningful behavioral transformation is shown to depend on factors such as governance quality, regulatory enforcement, and stakeholder scrutiny. This review contributes to the literature by clarifying the conditions under which sustainability reporting moves beyond disclosure toward genuine accountability, while identifying research gaps related to emerging economies, sectoral variations, and the integration of sustainability reporting with internal governance mechanisms. Keywords: Sustainability reporting; Corporate behavior; Accountability; ESG disclosure ABSTRACT Peningkatan perhatian terhadap sustainability reporting telah menjadikan pelaporan non-keuangan sebagai instrumen utama dalam mendorong transparansi dan akuntabilitas perusahaan. Lebih dari sekadar sarana komunikasi, sustainability reporting diharapkan mampu memengaruhi perilaku perusahaan melalui perubahan dalam pengambilan keputusan manajerial, orientasi strategi, dan praktik organisasi. Artikel ini menyajikan tinjauan literatur yang mensintesis penelitian-penelitian sebelumnya mengenai hubungan antara sustainability reporting dan perilaku perusahaan dalam bidang akuntansi, manajemen, dan keberlanjutan. Hasil kajian menunjukkan bahwa sustainability reporting berpotensi meningkatkan akuntabilitas, kesadaran risiko, serta orientasi jangka panjang perusahaan, namun dampak perilakunya masih bersifat tidak merata dan sangat bergantung pada konteks. Sejumlah studi menemukan bahwa praktik pelaporan keberlanjutan sering kali didorong oleh tekanan legitimasi dan institusional, sehingga menghasilkan pengungkapan yang bersifat simbolik dibandingkan perubahan organisasi yang substantif. Efektivitas sustainability reporting dalam mendorong perubahan perilaku yang nyata dipengaruhi oleh kualitas tata kelola, kekuatan regulasi, dan tingkat pengawasan pemangku kepentingan. Literatur review ini berkontribusi dengan memperjelas kondisi di mana sustainability reporting dapat bergerak dari sekadar pengungkapan menuju akuntabilitas yang bermakna, serta mengidentifikasi peluang riset lanjutan di negara berkembang dan lintas sektor. Kata Kunci: Sustainability reporting; Perilaku perusahaan; Akuntabilitas; Pengungkapan ESG